The highest intensity and the shortest duration permitting attainment of maximal oxygen uptake during cycling: effects of different methods and aerobic fitness level - Caputo, Fabrizio [UNESP]; Denadai, Benedito Sergio [UNESP] (Springer, 2008)
The aims of this study were: (1) to verify the validity of previous proposed models to estimate the lowest exercise duration (T (LOW)) and the highest intensity (I (HIGH)) at which VO(2)max is reached (2) to test the hypothesis that parameters involved in these models, and hence the validity of these models are affected by aerobic training status. Thirteen cyclists (EC), eleven runners (ER) and ten untrained (U) subjects performed several cycle-ergometer exercise tests to fatigue in order to determine and estimate T (LOW) (ET (LOW)) and I (HIGH) (EI (HIGH)). The relationship between the time to achieved VO(2)max and time to exhaustion (T (lim)) was used to estimate ET (LOW). EI (HIGH) was estimated using the critical power model. I (HIGH) was assumed as the highest intensity at which VO2 was equal or higher than the average of VO(2)max values minus one typical error. T (LOW) was considered T (lim) associated with I (HIGH). No differences were found in T (LOW) between ER (170 +/- 31 s) and U (209 +/- 29 s), however, both showed higher values than EC (117 +/- 29 s). I (HIGH) was similar between U (269 +/- 73 W) and ER (319 +/- 50 W), and both were lower than EC (451 +/- 33 W). EI (HIGH) was similar and significantly correlated with I-HIGH only in U (r = 0.87) and ER (r = 0.62). ET (LOW) and T (LOW) were different only for U and not significantly correlated in all groups. These data suggest that the aerobic training status affects the validity of the proposed models for estimating I (HIGH).
Keywords: oxygen uptake response; aerobic training status; severe-intensity domain